Meta-Analysis of the Effect of Dietary Sodium Restriction with or without Concomitant Renin-Angiotensin-Aldosterone System–Inhibiting Treatment on Albuminuria - D’Elia, Lanfranco (Clin J Am Soc Nephrol, 2015)
BACKGROUND AND OBJECTIVES: Urinary albumin excretion and/or albumin to creatinine ratio are associated with CKD and higher risk of cardiovascular events. Several studies investigated the effect of reduced dietary sodium intake on urinary albumin excretion and/or albumin to creatinine ratio in adult patient populations, but the majority was inconclusive because of insufficient statistical power. A meta-analysis of the randomized, controlled trials available could overcome this problem and lead to more definitive conclusions. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: A systematic search of the online databases available (from 1996 to October of 2014) was conducted of randomized, controlled trials that expressed urinary albumin excretion or albumin to creatinine ratio as the difference between the effects of two different sodium intake regimens. For each study, the mean difference and 95% confidence intervals were pooled using a random effect model. Heterogeneity, publication bias, subgroup, and meta-regression analyses were performed. RESULTS: Eleven studies met the predefined inclusion criteria and provided 23 cohorts with 516 participants and 1–6 weeks of follow-up time. In the pooled analysis, an average reduction in sodium intake of 92 mmol/d was associated with a 32.1% (95% confidence interval, −44.3 to −18.8) reduction in urinary albumin excretion. The effect of sodium restriction was higher in the cohorts including patients on concomitant renin-angiotensin-aldosterone system–blocking therapy, in the studies with intervention lasting at least 2 weeks, and among participants with evidence of kidney damage. A greater reduction of urinary albumin excretion was associated with a higher decrease in BP during the intervention. The analysis of changes in albumin to creatinine ratio provided similar results. CONCLUSIONS: This meta-analysis indicates that sodium intake reduction markedly reduces albumin excretion, more so during concomitant renin-angiotensin-aldosterone system–blocking therapy and among patients with kidney damage.